A new paradigm in polymerization induced self-assembly (PISA): Exploitation of "non-living" addition–fragmentation chain transfer (AFCT) polymerization. Issue 29 (6th July 2017) - Zhou, Dewen; Kuchel, Rhiannon P.; Zetterlund, Per B.
Abstract : Polymerization-induced self-assembly (PISA) is conducted based on "non-living" radical dispersion polymerization in the form of addition–fragmentation chain transfer (AFCT) polymerization. Abstract : Polymerization-induced self-assembly (PISA) is conducted based on "non-living" radical dispersion polymerization in the form of addition–fragmentation chain transfer (AFCT) polymerization. AFCT polymerization of benzyl methacrylate in ethanol using a polymeric AFCT agent comprising poly(ethylene glycol) methyl ether methacrylate generates an amphiphilic copolymer which subsequently self-assembles into various morphologies. This novel approach may expand the scope of PISA for synthesis of sulfur-free polymeric (nano)particles.